Παραγωγή Εκπαιδευτικού Υλικού με Εφαρμογές της Αλληλεπιδραστικής Βιβλιοθεραπείας σε Πολυπολιτισμικές Ομάδες - Καπραβέλου Αλεξία (Παιδαγωγικά ρεύματα στο Αιγαίο, 2022)
Bibliotherapy is the personal development or personal problem solving through reading. It is suitable for every individual or group of any age and ability. Bibliotherapy can be divided into clinical-remediate or preventive-developmental and into self-helping or interactive bibliotherapy. During an educational intervention in an immigrants’ voluntary school in the city of Volos, I used pre-designed bibliotherapeutic teaching equipment (e.g. excerpts from appropriate literature, issues for discussion and activities) in order to facilitate female immigrant mature students who are occupied as domestic workers in Greece to externalize their emotions. The material from this educational intervention formed the corpus for a case study – qualitative research. The domestic workers who participated in five bibliotherapeutic sessions seemed to prefer a non-fiction, informational book about problems at work and in social life rather than a fiction book. Nevertheless, we claim that through literature they may gain some emotional benefits, as they tend to identify themselves with the hero and they eventually develop empathy, a realistic view of their problems in life, as well as a more dynamic attitude regarding social demands and decision making.